A07 CircHTT, a novel circular rna molecule from the huntington's disease gene locus: functional characterization and pathophysiological implications. (12th September 2022) - Morandell, J; Döring, J; Monziani, A; Oss Pegorar, C; Ferrari, S; Bergonzoni, G; Tripathi, T; Di Leva, F; Kerschbamer, E; Mattis, VB; Rosati, J; Dieterich, C; et al.
Abstract : Circular RNAs (circRNAs), single-stranded, circularized RNA molecules, are particularly enriched in neurons and their functional relevance for brain development and neurological disorders has become evident in recent years. Here, we identified and validated the first brain enriched RNA circle originating from the human HTT locus (CircHTT: 484nt, Ex 2-6), conserved also in mouse (circHtt) and minipig. We validated the circularity of the identified molecule by divergent primer amplification, sequencing and RNase R treatment. Then, we analyzed the expression pattern of circHTT/circHtt in human and mouse tissues. This analysis revealed ubiquitous expression in different tissues, including blood. Importantly, and in line with circRNA characteristics, circHTT/circHtt is expressed at very high levels in the brain. To characterize possible implications for Huntington's Disease (HD), we studied its expression pattern in induced pluripotent stem cell (iPSC)-derived neuronal cells and HD mouse models. We found that circHTT/circHtt expression increases significantly with increasing number of CAG repeats in terminally differentiated cortical neurons and in brain districts of HD mouse models. These findings suggest possible implications for HD pathology. Analysis of circHTT sequence revealed week miRNA recognition elements, binding sites for RNA binding proteins, and the presence of a putative IRES sequence. Follow-up in vivo knock-down and in vitro over-expression studies are currently ongoing to elucidate the biological function(s) of circHTT/circHtt. In conclusion, we uncovered a circRNA sensitive to the HD mutation, which may be relevant for HD pathophysiology or to modulate huntingtin expression.